A phase 1 study of NY-ESO-1 vaccine + anti-CTLA4 antibody Ipilimumab (IPI) in patients with unresectable or metastatic melanoma. (1st January 2021) - Slingluff, Craig L.; Zarour, Hassane M.; Tawbi, Hussein Abdul-Hassan; Kirkwood, John M.; Postow, Michael A.; Friedlander, Philip; Devoe, Craig E.; Gaughan, Elizabeth M.; Mauldin, Ileana S.; Olson, Walter C.; Smith, Kelly T.; Macri, Mary J.; et al.
ABSTRACT: Ipilimumab (IPI) can enhance immunity to the cancer-testis antigen NY-ESO-1. A clinical trial was designed to assess safety, immunogenicity, and clinical responses with IPI + NY-ESO-1 vaccines and effects on the tumor microenvironment (TME). Patients with measurable NY-ESO-1 + tumors were enrolled among three arms: A) IPI + NY-ESO-1 protein + poly-ICLC (pICLC) + incomplete Freund's adjuvant (IFA); B) IPI + NY-ESO-1 overlapping long peptides (OLP) + pICLC + IFA; and C) IPI + NY-ESO-1 OLP + pICLC. Clinical responses were assessed by irRC. T cell and Ab responses were assessed by ex vivo IFN-gamma ELIspot and ELISA. Tumor biopsies pre- and post-treatment were evaluated for immune infiltrates. Eight patients were enrolled: 5, 2, and 1 in Arms A-C, respectively. There were no DLTs. Best clinical responses were SD (4) and PD (4). T-cell and antibody (Ab) responses to NY-ESO-1 were detected in 6 (75%) and 7 (88%) patients, respectively, and were associated with SD. The breadth of Ab responses was greater for patients with SD than PD ( p = .036). For five patients evaluable in the TME, treatment was associated with increases in proliferating (Ki67 + ) CD8 + T cells and decreases in RORγt + CD4 + T cells. T cell densities increased for those with SD. Detection of T cell responses to NY-ESO-1 ex vivo in most patients suggests that IPI may have enhanced those responses. Proliferating intratumoral CD8 + T cells increased after vaccination plus IPI suggesting favorable impact of IPI plus NY-ESO-1 vaccines on the TME. List of Abbreviations : Ab = antibody; CTCAE = NCI Common Terminology Criteria for Adverse Events; DHFR/DHRP = dihydrofolate reductase; DLT = Dose-limiting toxicity; ELISA = enzyme-linked immunosorbent assay; IFA = incomplete Freund's adjuvant (Montanide ISA-51); IFNγ = Interferon gamma; IPI = Ipilimumab; irRC = immune-related response criteria; mIFH = multispectral immunofluorescence histology; OLP = NY-ESO-1 overlapping long peptides; PBMC = peripheral blood mononuclear cells; PD = Progressive disease; pICLC = poly-ICLC (Hiltonol), a TLR3/MDA-5 agonist; RLT = Regimen-limiting Toxicity; ROI = regions of interest; RT = room temperature; SAE = serious adverse event; SD = stable disease; TEAE = treatment-emergent adverse events; TLR = toll-like receptor; TME = tumor microenvironment; TRAE = treatment-related adverse events.